Green HRM and Leadership Impact on Green Voice Behavior: Job Embeddedness as Mediator - Rifqi Zufar Saputro; Aryana Satrya (Eduvest - Journal of Universal Studies, 2026)
Employee participation is a crucial aspect of company operations that can influence corporate policies and decisions. Trade unions, as organizations representing workers, play a vital role in voicing workers' concerns and mediating the relationship between employees and the company. This research aims to examine the impact of green human resource management and green servant leadership on green voice behavior, with job embeddedness as a mediator. Data were collected through questionnaires completed by 247 trade union members in Indonesia, including both leaders and members. The questionnaires utilized a 7-point Likert scale. A quantitative research approach was applied, employing Structural Equation Modelling (SEM) to analyze the relationships between variables. The results indicate that green human resource management and green servant leadership have a significant and positive impact on green voice behavior. Furthermore, job embeddedness mediates the relationship between green human resource management and green servant leadership on green voice behavior. Based on these findings, companies are encouraged to develop environmentally focused human resource policies and for leaders to adopt environmentally conscious principles to motivate employees to voice opinions, ideas, and suggestions centered on environmental sustainability.